Hedonic hunger as a mechanism of action in outpatient cognitive behavioral therapy for bulimia nervosa. Issue 9 (7th July 2020) - Felonis, Christina R.; Juarascio, Adrienne S.
Abstract: Objective: Hedonic hunger (i.e., the motivation to consume palatable foods in the absence of an energy deficit) has been associated with the onset and maintenance of loss of control (LOC) eating. However, it remains underexplored as a mechanism of action in outpatient cognitive behavioral therapy (CBT) for bulimia nervosa (BN). In the present study, we hypothesized that reductions in hedonic hunger would significantly mediate reductions in overall eating pathology and LOC episodes in two samples ( N 1 = 28, N 2 = 23) of 20 and 16 sessions, respectively. Method: Participants completed the Eating Disorder Examination (EDE) and Power of Food Scale (PFS) at pre‐ and post‐treatment. Results: In both samples, EDE Global scores, LOC episodes, and PFS Total scores significantly improved over the course of treatment. In Sample 1, significant indirect effects of PFS Total scores on EDE Global scores and LOC episodes were observed. In Sample 2, the indirect effect of PFS Total scores was significant on EDE Global scores and nonsignificant on LOC episodes though it followed a similar pattern of change. Discussion: Results suggest that reductions in hedonic hunger are associated with better outcomes in CBT for BN. Replication and further research is needed to elucidate the treatment components driving these reductions.